Effects of Lime Application Rates and Incubation Periods on Selected Chemical and Biological Soil Properties in Acidic Soils of Tsegede Highlands, Northern Ethiopia - Hadera, Abreha Kidanemariam (Soil Acidity Characterization and Effects of Liming and Chemical Fertilization on Microbial Growth, Nutrient Uptake and Yield of Wheat (Triticum aestivum L.): The Case of Acidic Soils in Tsegede District, Northern Ethiopia, Edition 1, 2024)
An incubation experiment was carried out on two acidic soils collected from Tsegede highlands, northern Ethiopia, to evaluate the effects of applied lime levels on soil acidity (pH, exchangeable acidity, and Al) available P, micronutrients (Fe, Mn, Zn, and Cu) and microbial growth (fungi and bacteria). The treatments used were four rates of lime (0, 1, 2, and 3 times the recommended rate) and three incubation periods (30, 60, and 90 days) laid down in a completely randomized design replicated 4 times. The amount of lime recommended for the experimental soils 1 and 2 were 6 and 8 t ha-1, respectively. The analytical results showed that, on average, acidic soils supplied with the 7, 14, and 21 t ha-1 lime showed significant (P \(\le\) 0.05) increments by 0.42, 1.00, and 1.59 units in soil pH over the control, respectively. However, soil pH was observed to decline appreciably with increasing the incubation periods. Following the 90 days incubation period, soil available P increased by 80, 130 and 170%; extractable Fe decreased by 26, 31 and 34% and Mn by 55, 71 and 77% compared to the control, with the application of the 7, 14 and 21 t ha-1 lime, respectively. Likewise, bacterial growth significantly augmented by 42, 53, and 63%, in that order, whereas fungal growth did not show any significant difference. Furthermore, soil pH showed a significant and positive correlation with available P (r = 0.860**), Cu (r = 0.661**), and growth of bacteria (r = 0.788**) while a negative correlation with extractable Fe (r = -0.706**), Mn (r = -0.816**) and growth of fungi (r = 0.537**). Thus, it is suggested that the soil pH of the Tsegede highlands should be maintained at about 6, so as not to affect the availability of phosphorus, micronutrients and the growth of essential microorganisms.